Epidemiology and Mechanism of Drug Resistance of Multidrug-Resistant Klebsiella Pneumoniae Isolated from Patients with Urinary Tract Infection in Beijing Teaching Hospital, China - Xie Z; Jian J; Chen L (Infection and Drug Resistance)
Zeqiang Xie,1– 3 Jiyong Jian,1– 3 Liang Chen1– 3 1Clinical Laboratory Medicine, Beijing Shijitan Hospital, Capital Medical University, Beijing, People’s Republic of China; 2Peking University Ninth School of Clinical Medicine, Beijing, People’s Republic of China; 3Beijing Key Laboratory of Urinary Cellular Molecular Diagnostics, Beijing, People’s Republic of ChinaCorrespondence: Liang Chen, Clinical Laboratory Medicine, Beijing Shijitan Hospital, Capital Medical University, NO. 10, Tie Yi Road, Yang Fang Dian, Beijing, Haidian District, 100038, People’s Republic of China, Tel +86 18911726950, Email chenliang2254@bjsjth.cnPurpose: Klebsiella pneumoniae is an important pathogenic bacterium in causing urinary tract infection. With the overuse of antibiotics, bacteria resistant to quinolones combined with carbapenems are increasing. In this study, we investigated the epidemiology, molecular characteristics, drug resistance of multidrug-resistant Klebsiella pneumoniae (MDR-KPN) isolated from urine samples. It provides theoretical basis for the treatment of urinary tract infection by clinicians.Patients and Methods: Fifty-one strains of Klebsiella pneumonia were obtained from urine samples collected between 2012 and 2017 in total. All the strains are multi-drug resistant bacteria. This paper used multilocus sequence typing (MLST) to determine molecular epidemiological typing. We performed antimicrobial susceptibility testing and investigated quinolones and carbapenems resistance genes.Results: The strains which we collected were resistant to ciprofloxacin and Levofloxacin. In an epidemiological analysis using MLST, 86.27% (44/51) of isolates were confirmed to be ST11. The main carbapenem resistance gene was KPC-19, 78.43(40/51). Among the quinolone resistance genes, the major resistance genes were aac(6’)-Ib-cr, oqxA and oqxB.Conclusion: The main molecular epidemiological types we detected was ST11. The main resistance gene of carbapenems was KPC-19. The quinolone resistance genes are mainly aac(6’)-Ib-cr, oqxA and oqxB. The experimental results can help control the use of quinolones and carbapenems, and we could provide rational drug use basis for clinicians to treat urinary tract infection. For MDR-KPN, a combination of multiple antibiotics is necessary.Keywords: urinary tract infection, MLST, Klebsiella pneumoniae carbapenemase, quinolone resistance genes, Klebsiella pneumoniae